Primary Polydipsia in Children: Two Case Reports - Nu Ri Hwang; Min Sun Kim; Soon Chul Kim; Dae-Yeol Lee (Korean Society of Pediatric Nephrology, 2018)
Primary polydipsia (PP) is marked by an increase in thirst, and most often presents in patients with psychiatric illnesses. Although uncommon in children, we experienced cases of PP in a 15-month-old boy and a 5-year-old girl. Both were admitted to the hospital with symptoms of polydipsia and polyuria that appeared 1-3 months before admission. Brain magnetic resonance imaging in both patients was normal. A water restriction test was performed after hospitalization and showed normal results. The symptoms improved after the parents were instructed to implement water-intake restriction for 2 weeks. Our report provides useful information for the treatment of PP in children.